DEEP LEARNING APPROACH ENHANCES EDUCATIONAL QUALITY IN ELEMENTARY SCHOOLS - Hadi Wijaya; Endang Komara; Teti Ratnawulan (Universitas Islam Negeri Mataram, 2026)
This study is driven by the need for elementary schools to enhance educational quality through learning that goes beyond content mastery, fostering deep understanding, critical thinking, character development, and relevance to students’ real lives. The aim is to analyse the integration of deep learning to improve outcomes at SDN 01 Batunyala and SDN 02 Semayan. Using a qualitative approach with a multisite case study design, data were gathered through classroom observation, interviews with principals and teachers, document analysis, and learning activity documentation. Analysis employed the interactive model of data condensation, data display, and conclusion drawing. Findings reveal that deep learning can be integrated through three dimensions: mindful learning, meaningful learning, and joyful learning. These dimensions guide teachers in designing objectives, contextual activities, reflective questions, formative assessments, and feedback aligned with student needs. Integration of deep learning enhances cognitive, affective, social, and metacognitive outcomes. The study concludes that deep learning is a strategic pedagogical approach to strengthen elementary education when supported by teacher readiness, school leadership, contextual resources, and continuous academic supervision.